Computer Generation of Particle Solids - Greenspan, Donald; Rosati, Mario (University of Wisconsin-Madison Department of Computer Sciences, 1976)
A new particle approach for the study of solids is developed. The basic forces included are gravity and interparticle attraction and repulsion. Triangular and rectangular bodies are generated on the UNIVAC 1110 and various gross physical properties are verified.